2000
DOI: 10.1128/cdli.7.6.920-924.2000
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cytokine Secretion, Intracellular Protein Expression, and mRNA in Resting and Stimulated Peripheral Blood Mononuclear Cells

Abstract: Quantitation of cytokine production is a valuable adjunct to standard immunologic assays in defining several pathologic processes. Nevertheless, there is little agreement about which tissues should be assayed, which type of assay should be performed, and which stimulation protocol should be used. As these types of assays enter the clinical arena, there is need for standardization. There is also a need to maximize the amount of information which may be derived from a single sample. We compared secreted interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 23 publications
7
65
0
1
Order By: Relevance
“…Published studies have shown that ELISAs are generally reproducible, with a typical interassay variation of approximately 50% (2). The lower limit of detection for ELISA is 3 to 8 pg/ml (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Published studies have shown that ELISAs are generally reproducible, with a typical interassay variation of approximately 50% (2). The lower limit of detection for ELISA is 3 to 8 pg/ml (18).…”
Section: Methodsmentioning
confidence: 99%
“…Phorbol myristate acetate (PMA) (Sigma, St. Louis, Mo.) was used at a final concentration of 100 ng/ml for ELISA and RNA analysis, previously demonstrated to provide optimal conditions for the assay (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous ex vivo cytokine production by PBMCs has been reported not to occur in healthy individuals (2,4,7,21,22) or in persons with various disorders, including allergic asthma (4), active and inactive systemic lupus erythematosus (18), and sarcoidosis (6), and those recovering from vascular surgery (1). We ourselves have rarely, if ever, noted spontaneous cytokine production in PBMCs of healthy U.S. blood donors (reference 7 and unpublished data).…”
mentioning
confidence: 99%
“…It also serves as a valuable tool to monitor disease progression or inflammation (120,353). Some conventional methods available for cytokine measurement include radioimmunoassay (RIA) and ELISA.…”
Section: 347-352) the Effect Of Opioid Peptides On The Regulatimentioning
confidence: 99%